Gynaecological infections in paediatric and adolescent gynaecology: a review of recommendations - Plagens-Rotman, Katarzyna; Drejza, Michalina; Kędzia, Witold; Jarząbek-Bielecka, Grażyna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2021)
Inflammation within the genital organs in women is an important problem in gynaecology and venereology. Understanding the factors contributing to the inflammatory process and the role of defence mechanisms against their occurrence is important in terms of prevention and treatment. It is especially visible in paediatric gynaecology, where inflammatory diseases of the vulva, dermatoses, injuries and the effects of possible sexual harassment may overlap.